Cities, cultural policy and governance - Anheier, Helmut K, Ed; Yudhishthir Raj Isar, Ed (The cultures and globalization series ; 5, 2012)
"Today is a new metropolitan age and for the first time ever more people live in cities than they do anywhere else. As cities strengthen their international and cultural influence, the global world is acted out most articulately in the world's urban hubs - through its diverse cultures, broad networks and innovative styles of governance. Looking at the city through its internal dynamics, the book examines how governance and cultural policy play out in a national and international framework. Making a truly global contribution to the literature, editors Isar and Anheier bring together a truly international and highly-respected collection of scholars. In doing so, they skilfully steer debates beyond the city as an economic powerhouse, to cover issues that fully comprehend a city's cultural dynamics and its impact on policy including alternative economies, creativity, migration, diversity, sustainability, education and urban planning. Innovative in its approach and content, this book is ideal for students, scholars and researchers interested in sociology, urban studies, cultural studies, and public policy."--Publisher's website.